2019
DOI: 10.1038/s41598-019-45356-z
|View full text |Cite
|
Sign up to set email alerts
|

A universal fluorescence-based toolkit for real-time quantification of DNA and RNA nuclease activity

Abstract: DNA and RNA nucleases play a critical role in a growing number of cellular processes ranging from DNA repair to immune surveillance. Nevertheless, many nucleases have unknown or poorly characterized activities. Elucidating nuclease substrate specificities and co-factors can support a more definitive understanding of cellular mechanisms in physiology and disease. Using fluorescence-based methods, we present a quick, safe, cost-effective, and real-time versatile nuclease assay, which uniquely studies nuclease en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 76 publications
(79 reference statements)
0
5
0
Order By: Relevance
“… 1 In particular, the use of nuclease-activatable oligonucleotide probes (NAOPs) as biosensors has proven its potential as a groundbreaking solution in early diagnosis of serious infectious diseases. 2 , 3 The detection of bacterial infection, 4 6 malignant cells in biopsies of breast cancer, 7 9 or food contamination by pathogenic bacteria 1 has been previously reported to be feasible on the basis of their nuclease activity profile. 10 12 A key aspect in the development of any diagnostic tool based on oligonucleotide probes is the necessity of designing probes which are both efficient and specific.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 In particular, the use of nuclease-activatable oligonucleotide probes (NAOPs) as biosensors has proven its potential as a groundbreaking solution in early diagnosis of serious infectious diseases. 2 , 3 The detection of bacterial infection, 4 6 malignant cells in biopsies of breast cancer, 7 9 or food contamination by pathogenic bacteria 1 has been previously reported to be feasible on the basis of their nuclease activity profile. 10 12 A key aspect in the development of any diagnostic tool based on oligonucleotide probes is the necessity of designing probes which are both efficient and specific.…”
Section: Introductionmentioning
confidence: 99%
“…Nucleic acids have been proven useful recognition molecules for the development of several diagnostic strategies, taking advantage of their flexibility to be adapted to various transduction mechanisms, such as fluorescence, electrochemistry, piezoelectric, and colorimetric mechanisms . In particular, the use of nuclease-activatable oligonucleotide probes (NAOPs) as biosensors has proven its potential as a groundbreaking solution in early diagnosis of serious infectious diseases. , The detection of bacterial infection, malignant cells in biopsies of breast cancer, or food contamination by pathogenic bacteria 1 has been previously reported to be feasible on the basis of their nuclease activity profile. A key aspect in the development of any diagnostic tool based on oligonucleotide probes is the necessity of designing probes which are both efficient and specific . Efficiency is directly related to the extent to which the target nuclease cleavages the synthetic substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Next, we measured the peptides’ ability to bind and condense pDNA. Therefore, the complex formation process was further examined by using pDNA intercalating dye, which binds to the double-stranded DNA [ 18 ]. We observed that all of the peptides packed the pDNA already at the peptide concentration of 10 μM, corresponding to CR1.…”
Section: Resultsmentioning
confidence: 99%
“…The SAMDI-MS assay offers a label-free alternative toward measuring nuclease activities, including radioactivity 7 , 8 , 17 and fluorescence assays. 18 Eliminating the need for radionuclides offers a solution for handling the hazardous material, along with waste and safety concerns. Without a fluorescent reporter, the SAMDI-MS assay eliminates false positives that result from optical interference of library compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, fluorescent assays have emerged that use intercalation dyes that are removed upon nuclease activity, leading to a loss of signal. 18 While the assays offer a high-throughput readout and convenient reagents, these assays are prone to high rates of false-positive and/or false-negative results due to optical interference of library compounds.…”
Section: Introductionmentioning
confidence: 99%